(untitled) (Journal of Applied Oral Science, 2021)
Objective: This study aims to replicate the phenotype of Ltbp1 knockout mice in zebrafish, and to address the function of LTBP1 in craniofacial development. Methods: Whole mount in situ hybridization (WISH) of ltbp1 was performed at critical periods of zebrafish craniofacial development to explore the spatial-temporal expression pattern. Furthermore, we generated morpholino based knockdown model of ltbp1 to study the craniofacial phenotype. Results: WISH of ltbp1 was mainly detected in the mandibular jaw region, brain trunk, and internal organs such as pancreas and gallbladder. And ltbp1 colocalized with both sox9a and ckma in mandibular region. Morpholino based knockdown of ltbp1 results in severe jaw malformation. Alcian blue staining revealed severe deformity of Meckel's cartilage along with the absence of ceratobranchial. Three-dimension measurements of ltbp1 morphants jaws showed decrease in both mandible length and width and increase in open mouth distance. Expression of cartilage marker sox9a and muscle marker ckma was decreased in ltbp1 morphants. Conclusions: Our experiments found that ltbp1 was expressed in zebrafish mandibular jaw cartilages and the surrounding muscles. The ltbp1 knockdown zebrafish exhibited phenotypes consistent with Ltbp1 knockout mice. And loss of ltbp1 function lead to significant mandibular jaw defects and affect both jaw cartilages and surrounding muscles.